DEVELOPMENT OF A CUBESAT KIT FOR ACADEMIC PURPOSES: DESIGN, CONSTRUCTION, AND APPLICATIONS - Barros, Dafnhê Thor Castro de Martins (Seven Editora, 2026)
The disconnection between theory learned at school and the practical application of concepts in objects, items, or ideas that are apparently not tangible, such as a satellite, presents itself as a difficulty in the Brazilian educational system, aiming to bridge the gap between theory and the practical objective of science and technology education, while also seeking to spark curiosity and interest among teachers for technological development. This article begins with a bibliographic review to explore concepts and practices related to CubeSat kits for academic use. The practical part of the project involves building a CubeSat prototype that can be easily replicated and used by students with various levels of knowledge. By providing a complete and efficient CubeSat Kit, using PBL (Problem Based Learning) techniques, train a new generation of scientists and engineers, both developing technical skills and essential soft skills for the job market, such as teamwork, leadership ability, presentation skills, as well as to explore space and conduct innovative experiments.